FAKTOR-FAKTOR PENGHAMBAT IMPLEMENTASI KEBIJAKAN BUREAUCRATIC TRIMMING DI PEMERINTAHAN KOTA BUKITTINGGI - Elvira Mulya Nalien (Jurnal Kebijakan Pemerintahan, 2021)
Abstract The decision of the central government is unanimous, namely the Bureaucratic Trimming policy and must be immediately implemented by ministries / agencies as well as local governments. Although several K/Ls have completed implementing the simplification, it is not necessarily the case for local governments, including the Bukittinggi City Government. The dualism of directives and regulations from the Ministry of Empowerment of State Apparatus and Bureaucratic Reforms and the Ministry of Home Affairs hampered the implementation of this policy. So the purpose of this paper is to find out the inhibiting factors of the implementation of the Bureaucratic Trimming policy, especially in the Bukittinggi City Government. This is a qualitative research with data collection methods by means of in-depth interviews, non-participatory observation and review of related internal and external data sources. Determination of informants by means of purposive sampling. The findings where in the Communication Dimension, there are differences in the direction of the Minister of Empowerment of State Apparatus and Bureaucratic Reforms and the Minister of Home Affairs regarding the completion of the equalization of positions. The Resource Dimension, not all structural positions can be transferred to functional positions and the availability of several suitable functional positions. Furthermore, the loss of career patterns such as employee transfers and the fact that the simplification of the bureaucracy actually burdens the Bukittinggi City Budget. The dimensions of the Bureaucratic Structure, the finding of procedural confusion in terms of the focus of Bureaucratic Trimming, between prioritizing equalization of positions to functional or prioritizing simplifying structure. Finally, the Disposition Dimension, the Bukittinggi City Government fully complies with the central government's instructions by submitting a proposal for equalization of positions to functional in April 2021 to the Ministry of Home Affairs. However, with the issuance of Permenpan No. 17 of 2021, the city government of Bukittinggi is still waiting for further directions considering the guidance and supervision of the implementation of regional government is under the Ministry of Home Affairs. Keywords: Bureaucratic Trimming, Inhibiting Factors, Policy Implementation Abstrak Keputusan pemerintah pusat telah bulat yaitu kebijakan Penyederhanaan Birokrasi (Bureaucratic Trimming) dan harus segera dilaksanakan oleh kementerian/lembaga maupun pemerintah daerah. Meskipun beberapa K/L sudah rampung melaksanakan penyederhanaan dimaksud namun belum tentu bagi pemerintah daerah termasuk salah satunya Pemerintah Kota Bukittinggi. Adanya dualisme arahan maupun regulasi dari Kemenpan dan Kemendagri membuat implementasi kebijakan ini terhambat. Maka tujuan dari tulisan ini adalah untuk mengetahui faktor-faktor penghambat daripada implementasi kebijakan Bureaucratic Trimming khususnya di Pemerintah Kota Bukittinggi. Merupakan penelitian kualitatif dengan metode pengumpulan data dengan cara wawancara mendalam, observasi non partisipatif dan penelaahan sumber data internal maupun eksternal yang terkait. Penentuan informan dengan cara Purposive Sampling. Hasil temuan dimana pada Dimensi Komunikasi, terdapatnya perbedaan arahan Menpan RB dan Mendagri terkait penyelesaian penyetaraan jabatan Dimensi Sumber Daya, tidak semua jabatan struktural dapat dialihkan ke jabatan fungsional serta belum tersedianya beberapa jabatan fungsional yang cocok. Selanjutnya hilangnya pola karier seperti mutasi pegawai dan fakta bahwa penyederhanaan birokrasi justru membebankan APBD Kota Bukittinggi. Dimensi Struktur Birokrasi, ditemukannya kerancuan prosedur dalam hal fokus Bureaucratic Trimming, antara mengutamakan melakukan penyetaraan jabatan ke fungsional atau mendahulukan melaksanakan penyerderhanaan struktur. Terakhir Dimensi Disposisi, Pemerintah Kota Bukittinggi sepenuhnya mematuhi instruksi pemerintah pusat dengan telah menyampaikan pengusulan penyetaraan jabatan ke fungsional pada Bulan April 2021 ke Kemendagri. Namun dengan terbitnya Permenpan No. 17 Tahun 2021, pemkot Bukittinggi masih menunggu arahan lebih lanjut mengingat pembinaan dan pengawasan penyelenggaraan pemerintahan daerah adalah dibawah Kemendagri. Kata Kunci: Bureaucratic Trimming, Faktor Penghambat, Implementasi Kebijakan